2021
DOI: 10.3390/min11121387
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Uniaxial Compression Strength of Limestone Based on the Point Load Strength and SVM Model

Abstract: Uniaxial compression strength (UCS) is a fundamental parameter to carry out geotechnical engineering design and construction. It is simple and efficient to predict UCS using point load strength (PLS) at engineering sites. However, the high dispersion of rock strength limits the accuracy of traditional fitting prediction methods. In order to improve the UCS prediction accuracy, 30 sets of regular cylindrical specimen tests between PLS and UCS are conducted on limestone mines. The correlation relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, both the AI models possessed higher a degree of accuracy and can be applied where necessary. While comparing the performance of other AI models for stabilized soil mixes, it was revealed that the support vector machine (SVM) model prediction performance is significantly better than the traditional fitting function [42]. In another study a comparison was made between the results obtained by the prediction techniques.…”
Section: Prediction Performance Of Thementioning
confidence: 99%
“…However, both the AI models possessed higher a degree of accuracy and can be applied where necessary. While comparing the performance of other AI models for stabilized soil mixes, it was revealed that the support vector machine (SVM) model prediction performance is significantly better than the traditional fitting function [42]. In another study a comparison was made between the results obtained by the prediction techniques.…”
Section: Prediction Performance Of Thementioning
confidence: 99%
“…With the advances in computer-based algorithms, the geo-material strength indexes for different materials can be predicted and can achieve the expected level of reliability. Subsequently, many scientific researchers have launched various aspects of related research related to these predictions [8]. These studies have been implemented to complete the advancements of traditional procedures to estimate the geomechanical index properties of rock materials based on UCS, point-load [9], or Schmidt hammer [10] results.…”
Section: Introductionmentioning
confidence: 99%
“…In civil engineering, Grubbs' test was used to identify outliers in geotechnical data, such as soil properties, rock mechanics, and foundation performance [20,21]. Several studies applied Grubbs' test to find the possible outliers in the shear strength data of rock at the 5% confidence level [22,23]. Grubbs' test assumes that the data are normally distributed, which is why it may not be appropriate for datasets that are not normally distributed.…”
Section: Introductionmentioning
confidence: 99%